Pengaruh Inflasi Dan Tingkat Suku Bunga Terhadap Harga Saham Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Laili Afini; Salman Faris (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2023)
This study aims to determine the effect of inflation and interest rates on stock prices partially or simultaneously. The research was conducted on Banking Companies Listed on the Indonesia Stock Exchange.  The population in the study is a Banking Company Listed on the Indonesia Stock Exchange. Determination of the number of samples in this study using the samnpel selection table so as to obtain a total sample of 36 companies. Partially the Inflation and Interest Rate variables have an influence on the Stock Price variable. Both partially and simultaneously. Simultaneously the effect of Inflation and Interest Rates on Stock Prices is 39.1% and the rest is influenced by other variables not proposed in this study